Uji Antagonis Pyricularia grisea Sacc. Penyebab Blas pada Tanaman Padi menggunakan Jamur Rizosfer Isolat Lokal - Mukarlina, Meiniwati, Siti Khotimah, (Universitas Tanjungpura, 2014)
Blas caused by Pyricularia grisea Sacc. is one of disease on rice (Oryza sativa L.). The disease is controlled using bio-control agents which are antagonist to pathogenic fungi. The objective of this research was identify the fungi from rizosfer on rice and to the test their ability to suppress the growth of Pyricularia grisea Sacc. The research was carried out for July to September 2012 in the rice field in Kalimue Village, Keranji Paidang Village, Sengah Temila Sub-district, Landak Regency. Isolating Pyricularia grisea Sacc. was conducted based on direct plantation method. Dilution method and antagonism test using paired method are used to isolate rizosfer fungi. Antagonistic fungi like Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Curvularia sp., and Trichoderma harzianum were successfully isolated. The result showed the growth of Pyricularia grisea Sacc. was inhibited. The highest suppression shown by Trichoderma harzianum isolation was 88.63%.